2009
DOI: 10.1242/dev.032888
|View full text |Cite
|
Sign up to set email alerts
|

Pax6 is essential for lens fiber cell differentiation

Abstract: The developing ocular lens provides an excellent model system with which to study the intrinsic and extrinsic cues governing cell differentiation. Although the transcription factors Pax6 and Sox2 have been shown to be essential for lens induction, their later roles during lens fiber differentiation remain largely unknown. Using Cre/loxP mutagenesis, we somatically inactivated Pax6 and Sox2 in the developing mouse lens during differentiation of the secondary lens fibers and explored the regulatory interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 93 publications
10
102
1
Order By: Relevance
“…Additionally, Sipa1l3 or Epha4 deficiency resulted in an upregulation of the direct Wnt/β-catenin target axin2, which is in agreement with a previously published study that shows axin2 overexpression upon Wnt/β-catenin activation in mouse lenses (Antosova et al, 2013). These observations fit very well to published data showing that cataract formation, smaller lenses and inhibited lens cell differentiation can be induced by β-catenin overexpression (Antosova et al, 2013;Shaham et al, 2009;Martinez et al, 2009). Note that overexpression of β-catenin in LFCs alone is sufficient to induce cataract formation (Antosova et al, 2013).…”
Section: Sipa1l3 and Wnt Signalingsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, Sipa1l3 or Epha4 deficiency resulted in an upregulation of the direct Wnt/β-catenin target axin2, which is in agreement with a previously published study that shows axin2 overexpression upon Wnt/β-catenin activation in mouse lenses (Antosova et al, 2013). These observations fit very well to published data showing that cataract formation, smaller lenses and inhibited lens cell differentiation can be induced by β-catenin overexpression (Antosova et al, 2013;Shaham et al, 2009;Martinez et al, 2009). Note that overexpression of β-catenin in LFCs alone is sufficient to induce cataract formation (Antosova et al, 2013).…”
Section: Sipa1l3 and Wnt Signalingsupporting
confidence: 92%
“…Interaction of Epha4 and Sipa1l3 causes proper eye development through β-catenin-independent Wnt signaling In studies previously published by others, it has been shown that overexpression of β-catenin in LFCs results in an inhibition of LFC differentiation and cataract formation (Antosova et al, 2013;Shaham et al, 2009) that is similar to the Sipa1l3 LOF phenotype in the mouse (Greenlees et al, 2015). Gain of β-catenin function in the lens also leads to microphthalmia (Martinez et al, 2009) comparable to the loss of Sipa1l3 phenotype ( Fig.…”
Section: Loss Of Sipa1l3 and Epha4 Function Influence Early Eye Develmentioning
confidence: 75%
“…The transcription factor Pax6 is abundant in the LV and lens epithelium (Fig. 4C), with lower levels present in LFs (Shaham et al, 2009). The highest Pax6 levels are restricted to the anterior cells of the Prox1 cKO lens (Fig.…”
Section: Prox1 Cko Presumptive Lfs Appropriately Decrease Expression mentioning
confidence: 99%
“…BMP, FGF and Notch signaling pathways regulate lens fiber cell differentiation in conjunction with DNA-binding transcription factors, including FoxE3 (Blixt et al, 2007;Brownell et al, 2000;Medina-Martinez et al, 2005), Gata3 (Maeda et al, 2009), Pax6 (Shaham et al, 2009), Pitx3 (Ho et al, 2009;Medina-Martinez et al, 2009), Prox1 (Duncan et al, 2002;Wigle et al, 1999), Hey1 (Herp2) and Rbpj (Jia et al, 2007;Rowan et al, 2008). Although little is known about links between BMP and FGF signaling and these factors, disruption of Prox1 blocks expression of p27 Kip1 and p57 Kip2 in the posterior part of the lens vesicle, followed by arrested lens fiber cell elongation (Wigle et al, 1999).…”
Section: Kip2mentioning
confidence: 99%